Effects of increasing GleptoForte dosage on newborn piglet growth, litter performance, and blood parameters - Nichols, Gage E.; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
Newborn piglets have iron deficiencies due to inadequate iron storage and low levels of iron in mother’s milk. This results in lower red blood cell counts, lethargy, and mortality. Common industry practice is to administer 200mg of iron via injection at processing. Little is known of the iron level required for modern genetics and whether a booster shot is beneficial. Gelptoforte (Ceva Animal Health, LLC., Lenexa, KS) an injectable iron containing gleptoferron, is used in pigs to prevent anemia. This study evaluated the effects of increasing Gleptoforte dosage in suckling pigs and litter performance. 28 litters totaling 336 suckling pigs (DNA 241×600, initially 3.83 ± 0.114 lb BW), were equalized on each day of farrowing on a 21-d trial. During processing (d3), all piglets were weighed. Six barrows and six gilts per litter were allotted to treatment in a completely randomized design for a total of 56 piglets per treatment. Treatments consisted of a negative control receiving no iron injection and increasing levels of iron from Gleptoforte at 50, 100, 150, 200, or 200mg plus a 100mg booster at d11. Piglets were weighed at processing (d11) and weaning (d21) to calculate ADG. One barrow per treatment, per litter was utilized for blood collection via jugular venipuncture. Blood criteria included: Hemoglobin (Hgb), Hematocrit (Hct), Serum Fe, and Total Iron Binding Capacity (TIBC). Overall, ADG and ending BW improved (quadratic; P=0.001) as dosage increased. There was no evidence of difference for any hematological criteria measured on d3 prior to the iron injection. For all following blood data, a treatment × day interaction was seen. On d11 and d21 Hgb, and Hct increased (quadratic; P=0.001); Serum Fe increased (linear; P=0.001) on d11 and increased (quadratic; P=0.001) on 21; TIBC increased (quadratic; P=0.001) on d11 and increased (linear; P=0.001) on d21; with 0mg treatment having the lowest and 200mg treatment having the highest values, respectively. On d21, a significant difference was observed for Hct (P=0.046), Hgb (P=0.011) and serum Fe (P=0.019) between the 200mg and 200mg + 100mg treatments with the 200mg + 100mg resulting in the highest values. There was no evidence of TIBC differences between the 200mg and 200mg + 100mg treatments. In summary, no iron injection resulted in the poorest growth and blood parameters. Administering 100mg Gleptoforte resulted in the greatest growth performance. Administrating 200mg + 100mg Gleptoforte improved hematological criteria but did not influence piglet growth performance compared to 200mg.
Keywords: Fall 2017